2019
DOI: 10.3390/ph12020056
|View full text |Cite
|
Sign up to set email alerts
|

3-Vinylazetidin-2-Ones: Synthesis, Antiproliferative and Tubulin Destabilizing Activity in MCF-7 and MDA-MB-231 Breast Cancer Cells

Abstract: Microtubule-targeted drugs are essential chemotherapeutic agents for various types of cancer. A series of 3-vinyl-β-lactams (2-azetidinones) were designed, synthesized and evaluated as potential tubulin polymerization inhibitors, and for their antiproliferative effects in breast cancer cells. These compounds showed potent activity in MCF-7 breast cancer cells with an IC50 value of 8 nM for compound 7s 4-[3-Hydroxy-4-methoxyphenyl]-1-(3,4,5-trimethoxyphenyl)-3-vinylazetidin-2-one) which was comparable to the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 97 publications
(138 reference statements)
0
9
0
Order By: Relevance
“…Preliminary docking studies revealed that the vinyl substituent sits in the CBS. These results are promising for further development of the β-lactam structures as more stable analogues of CA-4 [72].…”
Section: -Vinyl Substituted β-Lactamsmentioning
confidence: 85%
“…Preliminary docking studies revealed that the vinyl substituent sits in the CBS. These results are promising for further development of the β-lactam structures as more stable analogues of CA-4 [72].…”
Section: -Vinyl Substituted β-Lactamsmentioning
confidence: 85%
“…The crystal structures of the imines 8h and 8i demonstrated the E configuration of the imines (Supplementary Materials Tables S1 and S13). The novel 3-(prop-1-en-2-yl)azetidin-2-ones (9a-p, 9r) were obtained by reaction of imines 8a-8r with 3,3-dimethylacryloyl chloride using the Staudinger reaction conditions with triethylamine as the base [60][61][62] (Scheme 1; Scheme 2). The β-lactam compounds (9t-v), were also prepared containing the 3,4,5-trimethoxyphenyl substituent (ring A) at the C-4 position, together with structurally related β-lactams 9w and 9x (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…19 Wang et al designed and synthesized three series of 3dienyl--lactams as inhibitors targeting a binding site of colchicine. 20 The imines 16 were accessed via butadienyl ketene generated in situ by the action of sorbic acid and suitable base in dichloromethane to afford 3-(buta-1,3dien-1-yl)azetidin-2-ones 17 (Table 5). Derivatives 17 also exhibited in vitro antitumor activity against the MCF-7 breast cancer cell line, with IC 50 values of 23-33 nM.…”
Section: Review Synopenmentioning
confidence: 99%
“…Derivatives 17 also exhibited in vitro antitumor activity against the MCF-7 breast cancer cell line, with IC 50 values of 23-33 nM. 20 Scheme 3 [4+2] cycloaddition of butadienyl ketene 4 and 1,3-diazabuta-l,3-dienes 25…”
Section: Review Synopenmentioning
confidence: 99%